The Sky's the Limit - Johnny Arnold (Symphony in the Flint Hills, 2012)
If you first meet Johnny Arnold over the phone and talk for more than five minutes, you’ll find yourself speaking with a Central Texas accent for the next week. And it’s “Johnny”---not Mr. Arnold. A Texas cattleman from Coryell County, near Gatesville, wh
Keywords: Johnny Arnold; cattle; ranch; cows; steer; Tommy Winters; farming; David Winters; Shorty Arnold; Inez Arnold; Frank Johnson; sale; native; stockers; Leet Pasture